Plan de negocios para la exportación a Valdivia-Chile de cerveza artesanal de café 100% colombiano (2020)
The purpose of this undergraduate project is to demonstrate the technical-financial viability of a business plan for the export of craft beer made with 100% Colombian coffee, for the city of Valdivia - Chile. All the pertinent study is carried out to identify the viability of the project, which includes the identification of the acceptance and the distribution possibilities of the product in the city of Valdivia, observing the advantages and disadvantages of its limitation, the required investments and the risks When carrying out this business plan, in order to find real results to validate this proposal. In addition, an economic study was carried out where all the expenses that are presented to achieve the export of the beverage are reviewed and a 5-year projection of the operations is made using financial tools such as net present value, the time of recovery of the investment and the calculation of the internal rate of return.